Indian Perspective on Antiplatelet De-escalation from Dual Antiplatelet Therapy to Single Antiplatelet Therapy – INDEPTH INSIGHT Survey - Mohan, Jagdish Chander; Oomman, Abraham; Shah, V T; Nath, Baishali (Cardiology and Cardiovascular Medicine, 2026)
Background: Dual antiplatelet therapy (DAPT) is used for secondary prevention after percutaneous coronary intervention (PCI), but prolonged use raises bleeding risk. De-escalation to single antiplatelet therapy balances ischemic protection and safety. Objective: This study aimed to assess cardiologists' knowledge, decisionmaking, treatment preferences and prescribing behaviors related to antiplatelet de-escalation in the Indian context. Methods: A cross-sectional survey involving 384 Indian cardiologists with 18 questions assessed awareness of genetic and platelet testing, de-escalation, clopidogrel resistance, and adverse events. Participation was voluntary, and responses were analyzed descriptively to reduce bias. Results: The survey demonstrated that 46.9% considered genetic testing relevant. However, its routine use remains limited, with greater reliance on platelet function testing (64.3%) and clinical judgement. High bleedingrisk (HBR) patients without genetic testing often switch to clopidogrel after 1-3 months (62.0%), while non-HBR patients typically use ticagrelor/prasugrel for 12 months (52.3%). Management of clopidogrel resistance followed guidelines, with 76.3% switching to another P2Y12 inhibitor. Most reported occasional (35.4%) transitions to prasugrel/ ticagrelor, while ticagrelor-to-clopidogrel switches were rare (38.5%). Adverse events (AEs) prompted therapy changes, with dyspnea (58.6%) being most common, leading to switching to clopidogrel. Major bleeding (70.4%), age ≥75 (39.2%), and low body weight (<60kg, 32.7%) caused prasugrel discontinuation. In patients on oral anticoagulation, clopidogrel was preferred initially (61.7%) and after DAPT (77.6%), emphasizing its safety. Triple therapy mainly preferred clopidogrel (86.5%). Conclusion: Indian cardiologists prefer clopidogrel for OAC and triple therapy, following guidelines. De-escalation depends on bleeding risk and resistance. Still, gaps persist in routine adoption of precision-guided approaches.